2019
DOI: 10.1103/physrevb.100.205403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excess charge carriers and fluid medium on the magnitude and sign of the Casimir-Lifshitz torque

Abstract: Last year, we reported a perturbative theory of the Casimir-Lifshitz torque between planar biaxially anisotropic materials in the retarded limit [Phys. Rev. Lett. 120, 131601 (2018)], which is applied here to study the change of sign and magnitude of the torque with separation distance in biaxial black phosphorus having excess charge carriers. The study is carried out both in vacuum as well as in a background fluid medium. The presence of extra charge carriers and that of an intervening fluid medium are both f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…[2,17,19,20,23,30,43]) to a more general case where retarded dispersion forces can reveal a very complex behaviour in media. For this reason, considerations of retardation effects are important for medium-assisted dispersion force experiments, for example Casimir experiments [16,23,43]; medium-assisted optical tweezers [44]; colloidal systems [45]; and in future measurements of the Casimir torque in a medium [46,47]. Beyond these impacts, we have shown that the near-field effect of dispersion forces in colloidal system yields an inhomogeneous particle density distribution near interfaces due to trapping potentials.…”
Section: Results and Conclusionmentioning
confidence: 98%
“…[2,17,19,20,23,30,43]) to a more general case where retarded dispersion forces can reveal a very complex behaviour in media. For this reason, considerations of retardation effects are important for medium-assisted dispersion force experiments, for example Casimir experiments [16,23,43]; medium-assisted optical tweezers [44]; colloidal systems [45]; and in future measurements of the Casimir torque in a medium [46,47]. Beyond these impacts, we have shown that the near-field effect of dispersion forces in colloidal system yields an inhomogeneous particle density distribution near interfaces due to trapping potentials.…”
Section: Results and Conclusionmentioning
confidence: 98%